The role of trust in financial robo-advisory adoption: A case of young retail investors in Pakistan - Zahid Bashir; Sadia Farooq; Muhammad Sabeeh Iqbal; Muhammad Aamir (Sustainable Futures)
This study examines the trust of retail investors in financial robo-advisory (FRA) services and their intent to adopt them in Pakistan. It also explores the moderating role of age on trust propensity and initial trust. Data were collected from 924 retail investors through an online survey. Partial least squares structural equation modeling (PLS-SEM) was used to analyze the data. Results show that trust propensity, perceived ability of FRAs, hedonic motivation, social influence, effort expectancy, facilitating conditions, and price value positively impact initial trust. However, effort expectancy negatively affects trust due to digital illiteracy and complex FinTech solutions in Pakistan. Younger retail investors exhibit higher levels of initial trust and adoption intent compared to older investors. This study contributes to the literature by extending the Unified Theory of Acceptance and Use of Technology (UTAUT) model to trust in FRAs. It highlights the moderating effect of age in an emerging market context. Practical implications include enhancing digital literacy, improving internet infrastructure, promoting price transparency, and addressing risk aversion. Policymakers and financial institutions should consider these findings to increase trust and adoption of FRAs. The study focuses on Pakistan, but future research could expand to other emerging markets.